The generals from defeat to victory, leadership in Asia, 1941-45 - Lyman, Robert (Constable & Robinson, 2008)
Presenting an account of war in Asia, this book analyses the effectiveness of the Japanese, British and American commanders who lead their forces in defeat and victory during the longest continuous campaign of the Second World War. It looks at the desperate struggle between both sides in what the British describe as 'the Forgotten War'.